Aesthetic Reconstruction of a Facial Defect After Subtotal Resection of the Parotid Gland Using a Superficial Circumflex Iliac Artery Pure Skin Perforator Flap. Issue 7 (29th October 2022) - Hashimoto, Kohei; Lee, Haesu; Tashiro, Kensuke
Abstract : Abstract: In the reconstruction of facial defects, thin and flexible coverage of the defect is desirable for cosmetic reasons. A free flap is 1 possible surgical option; however, a flap containing a fatty layer is bulky. in this study, the authors describe the reconstruction of a facial defect after subtotal parotidectomy for right parotid carcinoma using a superficial circumflex iliac artery pure skin perforator flap, with consideration given to facial contour. The superficial circumflex iliac artery pure skin perforator flap is a viable option to achieve the desired clinical and aesthetic outcome.